Analysis of learning motivation in improving learning outcomes in economics subjects between students of class XI social sciences and class XI natural sciences - Wibowo, Damaris Iqdam; Saputri, Dela Refi Novi; Mutmainah, Dwi; Yusida, Ermita; Sarmi, Sarmi (Program Pascasarjana Universitas Negeri Yogyakarta, 2021)
Learning motivation is one of the things that significantly affect student success in learning activities. The learning process that needs to be followed by learning motivation from students will cause the learning objectives to be achieved to be less than optimal. This study aims to determine the difference in learning motivation in improving economic learning outcomes between class XI students majoring in mathematics and social studies at Senior High School (SMA) Negeri Malang for the 2021/2022 academic year. The population of this study was 192 class XI students spread across six classes, namely five classes from the social studies department and 1 class from the mathematics department. Sampling using nonprobability sampling techniques for as many as 60 students. The research hypothesis is that there are differences in learning motivation in improving learning outcomes in economics subjects between students majoring in mathematics and social studies majors at SMA Negeri 6 Malang for the 2021/2022 school year. Data collection is carried out using questionnaires. This research is a comparative study. The data were analyzed using descriptive statistical analysis techniques. The study's descriptive analysis results showed that the average score of the learning motivation questionnaire survey results showed a difference in values of 0.53. Meanwhile, the average score of student learning outcomes shows a difference in grades of 0.5. Based on the results of this study, it can be concluded that the hypothesis is accepted, which means that there are differences in learning motivation in economics between students majoring in mathematics and social studies majors at SMA Negeri 6 Malang for the 2021/2022 academic year.